Molecular characteristic of alpha thalassaemia among patients diagnosed in UKM medical centre - Azma R.Z.; Ainoon O.; Hafiza A.; Azlin I.; Noor Farisah A.R.; Nor Hidayati S.; Noor Hamidah H. (Malaysian Society of Pathologists, 2024)
Alpha (α) thalassaemia is the most common inherited disorder in Malaysia. The clinical severity is dependant on the number of α genes involved. Full blood count (FBC) and haemoglobin (Hb) analysis using either gel electrophoresis, high performance liquid chromatography (HPLC) or capillary zone electrophoresis (CE) are unable to detect definitively alpha thalassaemia carriers. Definitive diagnosis of α-thalassaemias requires molecular analysis and methods of detecting both common deletional and non-deletional molecular abnormailities are easily performed in any laboratory involved in molecular diagnostics. We carried out a retrospective analysis of 1623 cases referred to our laboratory in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) for the diagnosis of α-thalassaemia during the period October 2001 to December 2012. We examined the frequency of different types of alpha gene abnormalities and their haematologic features. Molecular diagnosis was made using a combination of multiplex polymerase reaction (PCR) and real time PCR to detect deletional and non-deletional alpha genes relevant to southeast Asian population. Genetic analysis confirmed the diagnosis of α-thalassaemias in 736 cases. Majority of the cases were Chinese (53.1%) followed by Malays (44.2%), and Indians (2.7%). The most common gene abnormality was αα/--SEA (64.0%) followed by αα /- α 3.7 (19.8%), - α 3.7/--SEA (6.9%), αα/αα CS (3.0%), --SEA/--SEA (1.2%), - α 3.7/- α 3.7 (1.1%), αα/-α4.2 (0.7%), -α 4.2/--SEA (0.7%), -α3.7/-α 4.2 (0.5%), αα CS/-- SEA (0.4%), αα CS/ααCd59 (0.4%), ααCS/αα CS (0.4%), -α3.7/αα Cd59 (0.3%), αα/ααCd59 (0.1%), αα Cd59/ ααIVS I-1 (0.1%), -α3.7/ααCS (0.1%) and --SEA /αα Cd59 (0.1%). This data indicates that the molecular abnormalities of α-thalassaemia in the Malaysian population is heterogenous. Although α-gene deletion is the most common cause, non-deletional α-gene abnormalities are not uncommon and at least 3 different mutations exist. Establishment of rapid and easy molecular techniques is important for definitive diagnosis of alpha thalassaemia, an important prerequisite for genetic counselling to prevent its deleterious complications.